MAKNA QOLBUN SALIM PADA LAGU TERAMINIKARYA GHEA INDRAWARI - Sari, Pilga Ayong (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Raden Fatah Palembang, 2024)
This study aims to research the meanings of qolbun salim in Teramini song by Ghea Indrawari. The research method used is qualitative research. The primary data used are song lyrics. The secondary data is a literature study from various sources and literature, such as books, journals, and sources from the internet. This data is taken by listening to the song, writing down the lyrics, and classifying them. This study was conducted in several steps. First, understanding the song carefully, the flow of Teramini's song is carefully observed to understand the meaning conveyed by the singer to the listeners through the song. Second, recording the data that obtained from the song lyrics that show the signs and meanings of Qolbun Salim. Third, the data is classified into three, namely denotation, connotation and myth. Fourth, combining all the data results to get a conclusion about the meaning of Qolbun Salim in the lyrics of Teramini song. The results of this study indicate that this song has the meanings of qolbun salim as included in five basic terms, namely; Every human being must always have a patient, sincere heart, not easily discouraged, grateful and must always have faith and devotion to Allah SWT in living a life full of obstacles, challenges and tests.